The Sarbanes‐Oxley Act and Exit Strategies of Private Firms - Bova, Francesco; Minutti‐Meza, Miguel; Richardson, Gordon; Vyas, Dushyantkumar (Contemporary Accounting Research, 2014)
The costs and benefits of the Sarbanes‐Oxley Act of 2002 ( SOX ) have been oft‐debated since the inception of the Act. Much of the extant literature has assessed the costs and benefits of SOX to publicly traded companies. We focus on the costs of SOX compliance for private firms wanting to exit the private market via either an acquisition by a public firm or an IPO . Consistent with our predictions we establish two principal findings. First, SOX appears to have shifted the preferences of private firms from going public to exiting the private market via acquisition by a public acquirer. Second, private target deal multiples are increasing in variables that proxy for a private target's level of pre‐acquisition SOX compliance. These findings suggest that SOX ‐related costs have both restricted the action space of possible exit strategies for private firms and led to lower deal multiples for those private acquisition targets that are less likely to be SOX compliant prior to acquisition.